STRATEGI KOMUNIKASI PEMASARAN DIGITAL BERLANDASKAN TRI KAYA PARISUDHA DALAM MEMBANGUN BRAND AWARENESS PADA PRODUK KEKINIAN - Ida Ayu Nyoman Sutriani; Ni Kadek Keysia Citra Dharma (Sadharananikarana: Jurnal Ilmiah Komunikasi Hindu, 2026)
This study aims to analyze the Tri Kaya Parisudha-based digital marketing communication strategies used to build brand awareness for Kopi Keliling products in Mataram, the application of Tri Kaya Parisudha values in digital marketing communication activities, and the implications faced by business owners. This study employs a qualitative approach using descriptive methods. Data were collected through observation, in-depth interviews with business owners and consumers, and documentation of digital marketing activities. The results show that digital marketing communication strategies are implemented through the use of social media, the creation of informative and entertaining content, interaction with consumers, digital promotions, and the integration of various communication media. The application of these strategies has implications for strengthening brand awareness, brand association, perceived quality, and brand loyalty, although challenges remain in the form of digital competition, changing trends, limited resources, and the need for consistency between communication and actual actions. A digital marketing communication strategy based on Tri Kaya Parisudha can serve as an ethical, consistent, and sustainable approach to building brand awareness for Kopi Keliling in Mataram.